2013
DOI: 10.1021/jm4001709
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Benzimidazole-Based Glutaminyl Cyclase Inhibitors Featuring a Heteroaryl Scaffold

Abstract: Glutaminyl cyclase (hQC) has emerged as a new potential target for the treatment of Alzheimer's disease (AD). The inhibition of hQC prevents of the formation of the Aβ3(pE)-40,42 species which were shown to be of elevated neurotoxicity and are likely to act as a seeding core, leading to an accelerated formation of Aβ-oligomers and fibrils. This work presents a new class of inhibitors of hQC, resulting from a pharmacophore-based screen. Hit molecules were identified, containing benzimidazole as the metal bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 37 publications
(77 reference statements)
0
43
0
Order By: Relevance
“…They all contain zinc-binding group, a hydrogen-bonding donor and an aromatic group to interact with Phe325 in the pocket as a critical amino acid for potent binding. [18][19][20][21][22] Recently, a new binding pocket was reported with an orientation opposite to that of the Phe325 pocket, based on the discovery of SEN177. Crystal studies of the SEN177-hQC complex showed two interactions between the enzyme and the inhibitor in terms of inhibitor orientation: the pyridine ring with Trp207 and the uorine atom of 2-uoropyridine with the hydrogen atom of His330 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…They all contain zinc-binding group, a hydrogen-bonding donor and an aromatic group to interact with Phe325 in the pocket as a critical amino acid for potent binding. [18][19][20][21][22] Recently, a new binding pocket was reported with an orientation opposite to that of the Phe325 pocket, based on the discovery of SEN177. Crystal studies of the SEN177-hQC complex showed two interactions between the enzyme and the inhibitor in terms of inhibitor orientation: the pyridine ring with Trp207 and the uorine atom of 2-uoropyridine with the hydrogen atom of His330 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Among these types of compounds benzimidazole derivatives which are present in a wide variety of medicine such as albendazole, thiabendazole, omeprazole, carbendazim, mebendazole, timoprazole, and found naturally in the structure of vitamin B12 [30,31]. Different heterocyclic rings (like 1,2,4-triazole, 1,3,4-thiadiazole and oxadiazole) linked to benzimidazoles have been designated as an important pharmacophores and are well known for their diverse biological activities such as antibacterial, antiinflammatory, antiulcer, antioxidant, antitumor, lipase inhibition, glutaminyl cyclase inhibition, anti-enterovirus and anticancer activities [32][33][34][35][36][37]. Literature survey reveals that benzimidazole derivatives indicated appreciable antimycobacterial activity [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Using a different CD47 antibody (B6H12), we confirmed that overall CD47 protein expression and cell surface localization were not decreased upon transduction with sgRNAs targeting QPCTL (Figures 2D, E; Figure S4). We then tested two small molecule inhibitors of QPCTL, SEN177 29 and PQ912 [30][31][32] , to validate that the enzymatic activity of QPCTL is required for the observed loss of CC2C6 binding, but not B6H12 binding (Figures 2D, F, G;…”
mentioning
confidence: 99%